Coordinating Stabilization and Structural Reform : Proceedings of the Seminar Coordination of Structural Reform and Macroeconomic Stabilization, Washington, D.C., June 17-26, 1993. (International Monetary Fund, 1994)
This seminar volume, edited by Richard C. Barth, Alan R. Roe, and Chorng-Huey Wong, presents an overview of the links between structural and macroeconomic policies that were addressed in an IMF Institute seminar held in Washington, D.C., in 1993. The most important areas of structural reform are covered: the price system, tax and expenditure policy, exchange rate management, external trade, public enterprises, the financial sector, and social safety nets. Four case studies are presented: China, Poland, Argentina, and the Gambia.